2006
DOI: 10.1111/j.1525-1438.2006.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal carcinomatosis in endometrial clear cell carcinoma at initial presentation: a case report

Abstract: Bone metastasis is frequently seen in different solid tissue malignancies. However, it is a very rare entity in endometrial cancers and most of the previous reports were localized to a single bone. To the best of our knowledge, this is the first report of a case with disseminated bone metastasis from endometrial clear cell carcinoma. A 69-year-old, multiparous woman presented with the complaint of postmenopausal bleeding. Diagnostic workup revealed endometrial clear cell carcinoma. After comprehensive surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In cases of a single site of metastasis, local radiotherapy may be effective 27 and should be combined with surgery, such as for amputations described for calcaneal metastases. There seems to be evidence that radiotherapy improves the survival of these patients, while chemotherapy could be useful in patients with multiple bone metastases 31 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In cases of a single site of metastasis, local radiotherapy may be effective 27 and should be combined with surgery, such as for amputations described for calcaneal metastases. There seems to be evidence that radiotherapy improves the survival of these patients, while chemotherapy could be useful in patients with multiple bone metastases 31 …”
Section: Discussionmentioning
confidence: 99%
“…Palliative treatment with radiotherapy and chemotherapy is recommended, and has been related to the acceptable control of tumor size and pain 31 . This treatment mode is probably the best option in patients with several affected bones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A further review of the literature revealed 38 articles[ 2 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 ] between 1967 and 2011, describing 61 patients with metastatic endometrial cancer to bone. Including our case, these patients ranged in age from 32 to 86 years, with an average age of 62 years (standard deviation 10.8 years) [ Figure 6 ].…”
Section: Discussionmentioning
confidence: 99%